Reading Judie Oron’s Cry of the Giraffe: A Critique of Empire - Joshi, Bhup Raj (Mindscape: A Journal of English & Cultural Studies, 2025)
This article seeks identity of a racially segregated community and characters by critically examining racial discrimination, cultural erasure, and gendered oppression experienced by the Ethiopian-Jewish community known as Beta Israel through an in-depth analysis of the novel, Cry of the Giraffe by Judie Oron. The application of postcolonial theory has been used as the strategy in the research to explore how systemic racism operates across historical, political, and cultural contexts, and linking the lived experiences of Ethiopian Jews to global legacies of colonialism. The study integrates perspectives from Frantz Fanon on psychological violence, Homi Bhabha on hybridity and mimicry, Gayatri Spivak on subaltern silence, W.E.B. Du Bois on double consciousness, Edward Said on Orientalism and Joe Feagin on systemic racism. Historically marginalized within predominantly Christian Ethiopia, the Beta Israel endured centuries of exclusion, being labeled Falasha (stranger or landless) and denied land ownership, education, and political participation. Under Ethiopia’s Marxist regime, systemic persecution intensified through bans on Hebrew, closure of Jewish schools, economic sabotage, and targeted violence. The symbolic Cry of the Giraffe captures the unheard suffering of marginalized peoples, while acts such as preserving oral traditions, maintaining religious customs, and covertly resisting assimilation underscore community resilience.